Pengaruh Metode RGEC (Risk Profile, Good Corporate Governance, Earnings, dan Capital) Pada Nilai Perusahaan - Lestari, Desak Made Gita; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2018)
This research is purposed to determine the effect of the application of RGEC method to the value of the firm in the banking system. This research has 43 banks listed in Indonesia Stock Exchange for 3 consecutive years from 2014-2016, so the total sample is 129 samples by using purposive sampling method. From the analysis result obtained by using multiple regression analysis, it is found that risk profile variable has a negative effect on value of the firm, however the variable of good corporate governance, earnings, and capital has positive effect on value of the firm. Keywords : risk profile, GCG, earnings, capital, value of the firm